Change in Work–Time Control and Work–Home Interference Among Swedish Working Men and Women: Findings from the SLOSH Cohort Study - Leineweber, Constanze (Int J Behav Med, 2016)
PURPOSE: The aim is to study the influence of change in work–time control (WTC) on work–home interference (WHI) while adjusting for other work-related factors, demographics, changes at work and WHI at baseline among women and men. An additional aim was to explore sex differences in the relation between change in WTC and WHI. METHODS: The study included working participants of the Swedish Longitudinal Occupational Survey of Health (SLOSH) study of the third (2010) and fourth (2012) waves (n = 5440). Based on a seven-item index, four groups of WTC were formed: stable high (40 %), stable low (42 %), increasing (9 %), or decreasing (9 %) WTC over the 2 years. WHI was measured by four items and individuals were categorised in whether suffering or not suffering of WHI. Sex-stratified logistic regression analyses with 95 % confidence intervals (CI) were used to estimate the odds of experiencing WHI by change in WTC. RESULTS: Controlling for demographics and work-related factors, women with stable low (OR = 1.46; 95 % CI 1.14–1.88) and women and men with decreasing WTC (women OR = 1.99; 95 % CI 1.38–2.85; men OR = 1.80; 95 % CI 1.18–2.73) had higher odds of WHI than those with a stable high WTC. Additionally, adjusting for changes at work and WHI at baseline did not alter the results substantially. Interaction analysis did not reveal any significant sex difference in the relation between WTC and WHI. CONCLUSIONS: For both women and men decreased and for women only, low control over working hours resulted in WHI also after adjusting for work-related factors and demographics.